Impact of Multistory Housing Projects on the Urban Scene (Al-Muthana Airport street) (Journal of Planner and Development, 2026)
Multistory residential buildings are prominent visual elements that may be transformed by their location and design into distinctive urban landmarks that are harmoniously integrated into the existing urban fabric or, on the contrary, may contribute to the production of visual distortion leading to a break in the urban horizon and loss of visual coherence with the surrounding environment, and the city of Baghdad has witnessed since the millennium clear transformations in its urban scene, as the vertical extension began to manifest in multiple areas, especially in its vital center, which includes a number of buildings that predominate residential character, hence the research issue emerged on. The research hypothesis is that the introduction of these projects without adhering to planning and design standards leads to confusion and distortion in the visual and sensory perception of the urban scene. The research aims to understand the relationship between Multistory residential projects and the urban scene, increase planning awareness in choosing the locations of these projects, and develop vacant spaces in an integrated manner that supports urban and urban integration. Adopting a methodology based on the descriptive, analytical and field approach, the research concluded that the absence of appropriate architectural treatments, moving away from the principle of human scale, and weak integration of sustainability concepts and visual identity are all factors that negatively affect the perception and quality of the urban scene. The research recommended the need to develop a holistic vision to integrate residential vertical projects into the urban fabric while adopting design and planning standards based on visual perception and human scale.